Keresahan Rhoma Irama terhadap Peran Perempuan di Sektor Publik Kajian terhadap Lirik Lagu “Emansipasi Wanita” - Moh Muzakka (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The purpose of this study is to find Rhoma Irama's views on the role of women in the public sector in the lyrics of the song he wrote in the 1980s, namely "Women's Emancipation". To study Rhoma Irama's view, structural and feminism studies are used. Based on structural studies, the lyrics to the song "Emansipasi Wanita" are very aesthetic because they are built by strong sound elements and proper diction. With that strength, Rhoma Irama managed to convey her expression about her anxiety about the role of women in the public sector. In the lyrics that confuse nature and gender it is revealed that if the role of women in the public sector is very dominant, then the position of the patriarchy will be threatened and family life will also be damaged.